Bioethics for the training of biochemists and pharmacists - Quesada Delgado, Alexandra (Revista Universidad de Guayaquil, 2022)
The educational system of the University of Guayaquil incorporates Bioethics as a compulsory subject, in the third semester of the Faculty of Chemical Sciences, four units are addressed, with group and individual activities. The objective of this study is to carry out an analysis of training in bioethical guidelines, the teaching system and the student’s attitudinal achievements. A survey with 3 sections and 13 questions was applied using a questionnaire with a Likert-type scale, the validation of internal consistency showed a value of 0.99 for the Cronbach Alpha Correlation Coefficient, developed on the Office 365 platform, with the use of Form. 90 students who passed the subject in March 2021 and 62 in November 2021 participated. Incentive answers were found (agree and totally agree): change of attitude regarding the exercise of moral values for pre- and professional practice stands out 84.9%, with the subject of Bioethics, they have managed to receive a humanistic professional training with an emphasis "on a personalized and dignified treatment of the patient", 90.1%, teaching the subject in the Third Semester, 82.2% and 92.8% of those who responded that the teaching of Bioethics It must be participatory, collaborative and dynamic. The contribution of this research is expected to empower biochemists and pharmacists, reinforce their actions with foundations, ethics and dignity, encourage them to reflect for the well-being of our society.